Recovery Education for Adults Transitioning From Homelessness: A Longitudinal Outcome Evaluation - Durbin, Anna; Nisenbaum, Rosane; Wang, Ri; Hwang, Stephen W.; Kozloff, Nicole; Stergiopoulos, Vicky (Frontiers in Psychiatry, 2021)
Objective: Grounded in principles of adult education, Recovery Education Centres (RECs) hold promise in promoting recovery for adults with mental health challenges, but research on recovery outcomes for hard-to-reach populations participating in RECs is scant. This quasi-experimental study compares 12-month recovery outcomes of adults with histories of homelessness and mental health challenges enrolled in a REC, to those of participants of other community services for this population. Methods: This pre-post quasi-experimental study compared participants enrolled in a REC for people with histories of homelessness and mental health challenges (n = 92) to an age-and-gender frequency matched control group participating in usual services (n = 92) for this population in Toronto, Ontario. Changes from program enrollment to 12 months in personal empowerment (primary outcome), disease specific quality of life, recovery, health status, health related quality of life, and mastery were assessed. Post-hoc analyses compared subgroups with 1–13 h (n = 37) and 14+ h (n = 37) of REC participation during the study period to the control group. Linear mixed models estimated mean changes and differences in mean changes and 95% confidence intervals. Results: Mean change in perceived empowerment from program enrollment to 12 months in the intervention group [0.10 (95% CI: 0.04, 0.15)] was not significantly different from the control group [0.05 (−0.01, 0.11)], mean difference, 0.05 [(−0.03, 0.13), P = 0.25]. In the post-hoc analysis, the mean change in perceived empowerment for the intervention subgroup with 14+ h of REC participation [0.18 (0.10, 0.26)] was significantly different than in the control group [0.05 (−0.01, 0.11)] mean difference, 0.13 [(0.03, 0.23), P < 0.01]. Mean change in mastery was also significantly different for the intervention subgroup with 14+ h of REC participation [2.03 (1.04, 3.02)] vs. controls [0.60 (−0.15, 1.35)], mean difference, 1.43 [(0.19, 2.66), P = 0.02]. There were no significant differences in other outcomes. Conclusion: With sufficient hours of participation, recovery education may be a helpful adjunct to health and social services for adults with mental health challenges transitioning from homelessness.